2008
DOI: 10.3168/jds.2007-0940
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Effects of 2-Hydroxy-4-(Methylthio) Butanoic Acid Isopropyl Ester on Milk Production and Composition of Lactating Holstein Dairy Cows

Abstract: Sixteen multiparous Holstein cows were used to determine the effects of 2-hydroxy-4-(methylthio) butanoic acid isopropyl ester (HMBi: 0 vs. 1.26 g/kg of total ration dry matter (DM) and dietary crude protein (CP) concentration [14.7% (low) vs. 16.9% (standard), DM basis] on milk yield and composition using a replicated 4 x 4 Latin square design experiment with 4-wk periods. Cows were fed ad libitum a total mixed ration with a 1:1 forage-to-concentrate ratio (DM basis), and diets provided an estimated 6.71 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 6 publications
5
10
1
4
Order By: Relevance
“…DMI and hence also consumption of nutrients were the lowest in the diet containing MetaSmart TM (18.96 kg; M) in contrast to the diet containing Smartamine TM M, for which DMI was the highest (20.48 kg; S; P < 0.001). Several previous studies have failed to show significant effects of Met supplementation on DMI (Lara et al, 2006;Phipps et al, 2008;Ordway et al, 2009). However, some studies reported decreased feed intake (Johnson et al, 1999), in contrast with the findings of Xu et al (1998), who observed an increase in DMI for cows supplemented with Lys and Met.…”
Section: Dry Matter Intake and Milk Productioncontrasting
confidence: 50%
“…DMI and hence also consumption of nutrients were the lowest in the diet containing MetaSmart TM (18.96 kg; M) in contrast to the diet containing Smartamine TM M, for which DMI was the highest (20.48 kg; S; P < 0.001). Several previous studies have failed to show significant effects of Met supplementation on DMI (Lara et al, 2006;Phipps et al, 2008;Ordway et al, 2009). However, some studies reported decreased feed intake (Johnson et al, 1999), in contrast with the findings of Xu et al (1998), who observed an increase in DMI for cows supplemented with Lys and Met.…”
Section: Dry Matter Intake and Milk Productioncontrasting
confidence: 50%
“…Por su parte, Phipps et al (2008) al utilizar HMBi en dietas con dos concentraciones de PC (16,9 y 14,7%), no encontraron respuesta positiva en la producción láctea y lo asociaron a un faltante de proteína no degradable en el rumen o a algún aminoácido como la lisina, situación que pudo haberse presentado en el presente estudio, ya que la concentración de proteína no degradable en el rumen estuvo alrededor del 30% (como porcentaje de la PC) en las cuatro dietas utilizadas.…”
Section: Discussionunclassified
“…Otra situación que pudo afectar la falta de respuesta a la suplementación, fue la duración del experimento, ya que en estudios similares, el empleo de un cuadrado latino de solamente cuatro semanas de periodo experimental, pudo afectar la falta de respuesta obtenida en el experimento (Phipps et al, 2008). En otro experimento, St-Pierre y Sylvester (2005) obtuvieron un incremento en el rendimiento lácteo atribuible a una respuesta progresiva que alcanzó significancia a partir de la semana once de diecisiete semanas experimentales, razón por la que se puede Cuadro 6.…”
Section: Discussionunclassified
See 2 more Smart Citations